The development of canned pickled fish "Galonggong" (Decapterus macrosema) - Samaco, Madora G.
Canned pickled fish was developed from "galonggong", utilizing varying pretreatment and process time. The product was analyzed both objectively and subjectively. Heat penetration studies were also conducted to supplement the study on the optimum process time. Results showed that the preferred product was the one which was soaked in 15% brine and fried. Processing for 20 minutes at 212°F was found to be adequate for pickled fish packed in 2T (307 x 409) C-enamel cans. The standardized canned pickled "galongong" was described by the taste panel as firm, light brown in color, having a characteristic pickled fish odor and a too sour flavor. Judgements for general acceptability ranged from like moderately to like very much.